(3QSGdI aj LhGR JQGOa eaQO heQcHs - (3CHh GdMSf Hf CMeOs
(3ChdgG (B:s
(3GdMeO ddg QHGaY GdOQLGJ hHYO ajbhd deG WGd GdJTGLQ Hjf GdGYdGe ai LhGR JQGOa GdeaQO hGdeQcH s
(3BNQgG (B:s
(3hYfO PcQ GdVejQ jdGMX ef MjK gh eYfGg aGage Cf ef jRGd GbOGe GdGagGe s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdSGHY YTQs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGi (B(316) s
Keywords: (3GdadSaI hGdefWbs